Structural change towards services - Werner Hölzl (Austrian Institute of Economic Research (WIFO), 2021)
This paper examines broad patterns of structural change for a large number of countries on a global scale and for a smaller set of advanced industrialised countries over time. The findings show that structural change over the past decades followed the three-sector hypothesis. The past decades were characterised by the rise of the service sector, driven especially by business services and non-market service. At the same time as manufacturing sectors are declining in terms of shares, they remain the sectors with the highest contributions to aggregate productivity growth. An analysis of determinants of structural change confirms that country competencies related to institutional quality, knowledge generation and industrial application of the new knowledge are an important driving force of structural changes towards services, but that they have a heterogeneous impact on manufacturing subsectors. High technology manufacturing share seems not to be characterised by a tendency to decline with the development of country competencies. Broad policy implications are discussed.
Keywords: O11; O14; 330; Structural Change; Service Share; Manufacturing Share